2000
DOI: 10.1046/j.1365-4362.2000.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of skin diseases at the University Teaching Hospital, Addis Ababa, Ethiopia

Abstract: The pattern of skin diseases observed in this analysis shows that allergic and infectious causes account for three-quarters of skin problems. Emphasis should be given to this group of common skin diseases at all levels of health care so that proper diagnosis, treatment, and referral can be practiced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 7 publications
(17 reference statements)
11
29
1
Order By: Relevance
“…Our results show that female patients attend dermatology clinics more than males; similar results have been found in Norway, Egypt, Ethiopia, and India. 5,[14][15][16] As shown in Figure 1, female patients were more prevalent in each age group, except for the 45 to 54 and over-65s, we think that this is because females care about their appearance more than males, but lose this concern as they become older. The higher number of females can clearly be seen in the 15-24 group; this may be explained by the fact that during this period, acne has the highest incidence rate, causing unwanted cosmetics problems.…”
Section: Figure 2:-order Of Skin Diseases In Terms Of the Number Of Pmentioning
confidence: 99%
“…Our results show that female patients attend dermatology clinics more than males; similar results have been found in Norway, Egypt, Ethiopia, and India. 5,[14][15][16] As shown in Figure 1, female patients were more prevalent in each age group, except for the 45 to 54 and over-65s, we think that this is because females care about their appearance more than males, but lose this concern as they become older. The higher number of females can clearly be seen in the 15-24 group; this may be explained by the fact that during this period, acne has the highest incidence rate, causing unwanted cosmetics problems.…”
Section: Figure 2:-order Of Skin Diseases In Terms Of the Number Of Pmentioning
confidence: 99%
“…Accorsi et al 5 found that scabies infections were the leading cause of inpatient admissions in a northern Ethiopian hospital, where they accounted for 19.3% of total hospital admissions due to a skin disorder. At the Black Lion Teaching Hospital in urban Addis Ababa, Shibeshi 6 found that cutaneous infections were the second leading cause of disease among patients presenting with skin complaints after allergic skin diseases.…”
mentioning
confidence: 99%
“…This observation correlates well with other studies that report allergic skin diseases as the most common cause to seek care from a health provider. (4)(5)(6)(7) Among the allergic skin diseases observed, dermatitis was predominant. The breakdown of dermatitis subtypes has revealed a high frequency of contact dermatitis (33.9%).…”
Section: Discussionmentioning
confidence: 99%
“…(8) This was followed by atopic dermatitis while dyshidrotic dermatitis was found third, in contrast with other studies that report a low frequency of dyshidrotic dermatitis. (5) Urticaria represents a disease with a wide spectrum of causes. The patients attending our hospital suffered from either acute urticaria or exacerbations of chronic urticaria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation